Virtual reality with VRTK4 : create immersive VR experiences leveraging Unity3D and virtual reality toolkit - Baruah, Rakesh (Apress, 2020)
Virtual reality is quickly becoming the next medium to communicate your ideas. Once siloed in make-believe world of science fiction, virtual reality can now touch any aspect of your life. This book shows you how to create original virtual reality content using the Unity game engine and the Virtual Reality Tool Kit. By the end of the book you'll be creating your own virtual reality experience using the fundamental building blocks within. You'll start by reviewing spatial computing, an emerging field that encompasses self-driving cars to space exploration. You'll also create your own virtual reality environments for use on headsets such as those from Oculus and HTC. Using the Unity3D game engine and the Virtual Reality Toolkit on a computer or laptop, you will walk through the fundamentals of virtual reality with as little code as possible. That is the beauty of Unity and the Virtual Reality Toolkit. You will discover how to use buttons in a virtual space, gaze-tracking for user input, and physics for enabling interaction between a human and a virtual space. From game design to education to healthcare to human resources, virtual reality offers new and creative ways to engage users, students, patients, customers, and more. Not a coding book, Virtual Reality with VRTK4 shows that you don't need to be a computer or graphics whiz to begin creating your own virtual reality experiences. You will: Grasp Virtual Reality Toolkit and its interaction with Unity3D Explore the fundamental science of virtual reality Review the inner workings of Unity3D and its integration with VRTK Understand the big picture of C# coding in Unity3D Incorporate head and hand movement into virtual experiences.